River water quality assessment: Implementation of non-parametric tests for sampling frequency optimization - Naddeo, V.; Scannapieco, D.; Zarra, T.; Belgiorno, V. (Land use policy, 2013)
► 13 Italian rivers have been analyzed in order to assess their water quality. ► Environmental data trends have been developed using the Mann–Kendall statistical tool. ► A full characterization of 13 river water quality has been accomplished. ► Results showed that it is possible to reduce sampling frequency in several rivers. ► As a direct consequence, optimization of monitoring costs can be achieved. More than ten years ago, European Union defined guidelines for surface water quality with the 2000/60/EC Directive, or Water Framework Directive (WFD); this is one of the most important water legislation acts for both Member States and candidate countries, which aims to identify strategies in order to safeguard the EU environment. Main subjects of WFD are the control of pollution in watercourses and the definition of useful tools to help regional policy makers. The aim of the present study is to show in which way Water Framework Directive has been implemented into the Italian legislation, and then to focus on a case study, in which 13 Southern Italy rivers were investigated: sampling frequency of river water was evaluated as a promising parameter to be optimized. Results show that the optimization of this monitoring procedure could lead to reduction in sampling frequencies, when downward trends of macroindicators are found. Considering that the cost of water sampling and analysis has a significant role in water quality assessment, it is useful to point out that it is possible to obtain a reduction of the sampling cost if downward trends are shown, aiming then to redistribute resources to projects which require more effort.